Peran Humas Sebagai Fungsi Publikasi Dalam Mensosialisasikan Kegiatan Survei Seismik Pt Elnusa Tbk - Katry Anggraini; nur rachmah wahidah; Unik Desthiani (UMSU, 2021)
Public relations is the art of helping manage the objectives of an organization, the form of change that is facilitated in the organization, and a picture of philosophy. Public relations as a function of publication which has the ability to inspire everyone in achieving company goals. The activities of PT Elnusa Tbk's seismic survey made the public know and understand these activities. The purpose of this research is to determine the role of Public Relations as a publication function in socializing the seismic survey activities of PT Elnusa Tbk in 2D Selingsing, South Sumatra, to determine the persuasive communication of Public Relations as a function of publications in socializing the seismic survey activities of PT Elnusa Tbk in 2D Selingsing, South Sumatra, and for know the obstacles of PR as a publication function in socializing the seismic survey activities of PT Elnusa Tbk in 2D Selingsing, South Sumatra. This study uses a qualitative descriptive method. Data collected through interviews and field observations. In this research, it is concluded that from research to implementation of socialization activities carried out by the Public Relations of PT Elnusa Tbk have been well planned and carried out, where what is desired from the implementation in publishing PT Elnusa Tbk's seismic survey activities has been achieved. Conduct persuasive communication to communities affected by the seismic survey area in an open manner and door to door for those who are absent. Obstacles faced by PR when disseminating publications are residents who are absent and refuse, causing a long process of publishing the socialization of PT Elnusa's seismic survey in 2D Selingsing, South Sumatra.